On the So-called Akokoid/North-West Akokoid - Olaogun, Simeon (Journal for the Study of English Linguistics, 2022)
There have been three main contentious issues about the nine speech forms, christened Akokoid or north-west Akokoid in the North-western part of Akoko. These issues are: (1) the appropriate name for the speech forms (2) whether or not they are dialects of Yoruba or a distinct language, and (3) the internal relatedness of the speech forms. In an attempt to resolve these controversies, some existing scholarly works have come up with some proposals and suggestions. However, their proposed suggestions and solutions have not been able to sufficiently resolve the contentious issues. This being the case, this present study, leaning on history of migration, mutual intelligibility, syntactic evidence and neutrality hypothesis[1], advances fresh evidence and plausible arguments that would hopefully be generally acceptable and permanently resolve these lingering argumentations. Data for this study were elicited with syntactic checklist from purposefully selected native speakers, and were subjected to descriptive method of data analysis. [1] Neutrality hypothesis is used here to mean that the proposed name in this work is not suggestive of any linguistic affiliation with any of the communities where the language is being spoken.